2015
DOI: 10.1016/j.jhep.2014.10.044
|View full text |Cite
|
Sign up to set email alerts
|

Sofosbuvir plus ribavirin for the treatment of chronic genotype 4 hepatitis C virus infection in patients of Egyptian ancestry

Abstract: The findings from the present study suggest that 24 weeks of sofosbuvir plus ribavirin is an efficacious and well tolerated treatment in patients with HCV genotype 4 infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
115
1
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 153 publications
(130 citation statements)
references
References 22 publications
(28 reference statements)
13
115
1
1
Order By: Relevance
“…In the Egyptian ancestry trial, Ruane et al 38 enrolled 30 treatment-naive and 30 previously treated GT-4 patients who were treated for 12 weeks (n = 31) or 24 weeks (n = 29) with SOF and RBV. SVR12 was achieved in 68% of patients in the 12-week group and in 93% of patients in the 24-week group.…”
Section: Genotypes 4 5 Andmentioning
confidence: 99%
“…In the Egyptian ancestry trial, Ruane et al 38 enrolled 30 treatment-naive and 30 previously treated GT-4 patients who were treated for 12 weeks (n = 31) or 24 weeks (n = 29) with SOF and RBV. SVR12 was achieved in 68% of patients in the 12-week group and in 93% of patients in the 24-week group.…”
Section: Genotypes 4 5 Andmentioning
confidence: 99%
“…SOF plus RBV is an effective and well-tolerated treatment in patients of Egyptian ancestry and Egyptian patients chronically infected with genotype 4 HCV (Doss et al, 2015;Ruane et al, 2015). Yakoot et al (2015) reported that two generic SOF products (Grateziano or Gratisovir) are almost equally rapid and efficient in minimizing the HCV load in Egyptian patients.…”
Section: Discussionmentioning
confidence: 99%
“…When it was given for 12 wk without IFN as a dual therapy with RBV to HCVGT4 infected patients of Egyptian origin living in the United States, SVR rates of 79% and 59% were found in naïve and treatment experienced patients, respectively. Extending the treat ment for 24 wk yielded higher SVR rates: 100% and 93% [186] .…”
Section: Combination Therapy With Peg-ifn Rbv and Hcv Ns5b Polymerasmentioning
confidence: 95%